Pott's puffy tumor caused by Actinomyces naeslundii. (2020) - Bean, Holly; Min, Zaw; Como, James; Bhanot, Nitin
Abstract: Pott's puffy tumor is characterized by forehead swelling from subperiosteal abscess and frontal bone osteomyelitis. It is encountered mainly in children; rarely in adults. When it does occur in the latter population, the most common risk factors include head trauma, sinusitis, or cocaine abuse. Generally, the organisms thought to be involved include streptococci, staphylococci and oral anaerobic flora. We present a case of a 53 year old female who presented with forehead swelling of 3 month duration after a dental procedure, found to be secondary to Actinomyces naeslundii . Actinomyces is a very rare etiology of this disease and has been reported only twice earlier in the literature. We present an uncommon infectious disease along with summary of clinical characteristics of this entity in the adult population.